Studi Kasus: Asuhan Keperawatan Pada Anak dengan Meningitis - Sahla Rizky; IGA Dewi Purnamawati (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
Background: Meningitis is an infectious disease of the lining of the brain caused by viruses, bacteria, fungi and parasites. This disease can affect children from infancy to adolescence. Objective: This study aims to gain experience in providing nursing care to children with meningitis. The research method uses a descriptive case study method through a nursing process approach in providing nursing care to children with meningitis. Results: this study found clinical manifestations in the form of children having difficulty moving the right extremity, stabbing pain with a pain scale of five and feeling sore, intermittent pain, limp right hand and leg, CT scan results showed meningoencephalitis. Nursing problems found include impaired cerebral tissue perfusion, acute pain, impaired physical mobility, anxiety and risk of infection. Implementation of nursing in the form of monitoring increased intracranial pressure, monitoring pain scales, teaching distraction techniques, and assisting ambulation. Conclusion: children with meningitis require comprehensive care by involving all components to minimize disability in children.